A'ISYAH BINT AL-SYATHI DAN AL-TAFSIR AL-BAYANI LI AL-QUR'AN AL-KARIM (TELAAH METODOLOGI, ASBAB AL-NUZUL DAN ESKATOLOGI)) - Rahmah, Wahyuni Shifatur (IAINU Kebumen Prodi IAT, 2023)
Context analysis plays an important role in understanding revelatory events, because the concept of